Penerapan nilai pancasila dalam ekosistem ekonomi digital: Studi kasus start-up Indonesia - Abdillah, Abyannabil; Firdaus, Muhammad Hanif (Maliki Interdisciplinary Journal, 2025)
Five basic principles—One Godhead, Just and Civilized Humanity, Indonesian Unity, Democracy Led by Wisdom in Deliberation/Representation, and Social Justice for All Indonesian People—are found in Pancasila, the foundation of the Indonesian state, and serve as guidelines for national and state affairs. Apart from the diversity of the country, Pancasila functions as an intellectual foundation that upholds justice and togetherness. From the economic side, Pancasila supports the formation of a system based on the principles of the 1945 Constitution, namely social justice and kinship. The implementation of Pancasila’s ideals in the digital era is complicated by the digital economy and startup businesses. Startups can create innovative concepts based on technology, and the digital economy, which leverages contemporary networks and information technology, enables the growth and efficiency of international markets. Implementation of the principles of Pancasila by economic excavation